2008
DOI: 10.1103/physrevlett.100.035302
|View full text |Cite
|
Sign up to set email alerts
|

Quenched Dislocation Enhanced Supersolid Ordering

Abstract: I show using Landau theory that quenched dislocations can facilitate the supersolid (SS) to normal solid (NS) transition, making it possible for the transition to occur even if it does not in a dislocationfree crystal. I make detailed predictions for the dependence of the SS to NS transition temperature Tc(L), superfluid density and dislocation spacing L, all of which can be tested against experiments. The results should also be applicable to an enormous variety of other systems, including, e.g., ferromagnets.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 21 publications
1
69
1
Order By: Relevance
“…In this work, we explain that the origin of superfluidity in solid 4 He is large local strain in the vicinity of crystalline defects. Superfluidity along dislocations or grain boundaries can quantitatively account for the superflow through 4 He crystals observed by Ray and Hallock [18].In the past several authors have speculated about the possibility of the stress-induced supersolidity [19,20,21], especially under hydrostatic decompression since quantum effects and vacancy delocalization are expected to increase at lower densities. The phenomenology missed the attraction between vacancies which destabilizes a dilute homogeneous gas of vacancies.…”
mentioning
confidence: 99%
“…In this work, we explain that the origin of superfluidity in solid 4 He is large local strain in the vicinity of crystalline defects. Superfluidity along dislocations or grain boundaries can quantitatively account for the superflow through 4 He crystals observed by Ray and Hallock [18].In the past several authors have speculated about the possibility of the stress-induced supersolidity [19,20,21], especially under hydrostatic decompression since quantum effects and vacancy delocalization are expected to increase at lower densities. The phenomenology missed the attraction between vacancies which destabilizes a dilute homogeneous gas of vacancies.…”
mentioning
confidence: 99%
“…In fact, the presence of quantum effects also in high-quality 4 He solid samples points in the direction of a nonconventional state of strongly correlated-defects; a model of this kind, based on a network of dislocations was developed in ref. 124, and the transition temperature turned out to depend strongly on the defect concentration. Obviously, this argument does not exclude the possibility that some other extrinsic-defect model might agree with experiments; we simply observe that a more natural explanation comes from the other possibility as follows.…”
Section: Discussionmentioning
confidence: 99%
“…124) He found that quenched dislocations can promote the transition from a normal solid to a supersolid even if the dislocation-free crystal is normal down to T ¼ 0 K.…”
Section: Phenomenological Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…29. This article focuses on the coupling between nanoscale structure and supersolidity. 26,27 As is well appreciated, elastic strain may fundamentally affect local and mesoscopic electronic, magnetic and structural properties. There is ample evidence for significant coupling amongst the electronic degrees of freedom with the lattice distortions in cuprates, manganites, and ferroelectrics.…”
Section: Introductionmentioning
confidence: 99%